Modifikasi Aerator Menjadi Pompa Sampling Udara untuk Memenuhi Standar ABBM di Jurusan Kesehatan Lingkungan Poltekkes Depkes Yogyakarta - Choirul Amri (Poltekkes Kemenkes Yogyakarta, 2009)
Air sampling pump represents the most important appliance in air quality monitoring. The Environmental Health Department of Polytechnic of Health, Yogyakarta has only two units of this appliance, meanwhile, the reference learningequipments standard is ten. This problem definitely do not support the practical learning process, so that it has to be resolved. As purchasing the new ones isnot an appropriate solution, a modification of aquarium air-pump (aerator) appliance becoming the sampling pump is a good effort because of its cheapness and feasibility. The objective of the study was reached by the following steps: 1) modifying the aerator as the air sampling pump, 2) validating the modified air sampling pump, and 3) studying the advantages and the weaknesses of the modified air sampling pump. The results of the study indicate that the aerator can be modified as air sampling pump, and the modified pump was precise and accurate (i.e. 1,00 ± 0,06 lpm, at a speed of 1 lpm). Furthermore, the modified pump has many advantages, that is: cheap, simple, light in weight, easy to use, easy to maintain, durable, and air-flow manageable.